Building bridges in the classroom: A view from the academy - Bell, M.; Gerber, P.; Evans, Philip (Thomson Reuters, 2014)
Over the past two decades, the rise of specialist practice in the area of construction law has led to – and been fostered by – a proliferation in construction law teaching. This article examines this trend, offering observations about what makes for “best practice” in teaching students across construction-related disciplines – lawyers, construction professionals, undergraduates and graduates – and how the academy can assist in building bridges between those disciplines.